PANDEMI COVID 19 SEBAGAI ALASAN FORCE MAJEURE DALAM PERSPEKTIF PERJANJIAN - Fida Nur Udkila (Universitas Borneo Tarakan, 2021)
World business activities, both national and global, have also received a huge impact due to the outbreak of the Corona 19 Virus Disease (Covid-19). Business activities are affected as an implication of a lockdown or social distancing policy. The issues raised, namely whether force majeure can be applied as a reason for postponement or cancellation of performance in contracts during the Covid 19 pandemic and what if the parties making the contract do not include the disease epidemic to be part of it. force majeure? The research method used is a normative juridical research method using primary and secondary legal materials with a qualitative analysis approach.Based on the results of the research, it can be ignored. Force majeure can be applied as a reason for postponing or cancellation of achievements in contracts during the Covid 19 pandemic. Only applies to debtors who are really in the situation, and not necessarily all debtors. Only try on debtors who have stage disruptions and are really constrained so that they are unable to fulfill their obligations in the agreement. Meanwhile, debtors who have regular and regular stages are not subject to force majeure as an excuse for not fulfilling their obligations. The state of force majeure during the Covid-19 period can only be used as an effort to apply for relief to creditors for not fulfilling their obligations according to the agreement because the debtor is indeed unable to fulfill it.In a contract, it is important to note that force majeure has been determined in the contents of the contract. However, the parties that make the contract do not include the epidemic of the disease outbreak does not help to become part of the coercive circumstances in the agreement, the party who declares it must comply with the law.